2023
DOI: 10.1002/pc.27928
|View full text |Cite
|
Sign up to set email alerts
|

Review on recent progress in epoxy‐based composite materials for Electromagnetic Interference(EMI) shielding applications

Annie Aureen Albert,
V. Parthasarathy,
P. Senthil Kumar

Abstract: The densely packed electronic components in electronic devices emit electromagnetic (EM) radiations, and the interaction of the emitted EM radiations with external EM signals of neighboring components leads to device malfunctions and also creates health issues in human beings. Particularly, in aircraft, EM interference is a serious threat that leads to disastrous outcomes. The shielding of electronic components is an ideal way to reduce the pollution of electromagnetic interference (EMI). The mechanism of EMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…The application of magnetic nanofillers in enhancing the EMI shielding performance of NFMs has been widely reported. This is because their quantum size effect, natural resonance, and microcurrent properties can improve the magnetic loss and electromagnetic shielding performance of composite NFMs. In the work of Yang et al, a bifunctional electrospun NFM (33 μm thickness) was reported, whose surface was modified with Fe 3 O 4 nanoparticles (NPs) and MXene nanosheets, demonstrating an excellent specific shielding efficiency (SE) of 9212.1 dB cm 2 g –1 in the 8–26.5 GHz frequency range. Anwar et al used electrospinning technology to synthesize CoFe 2 O 4 /C NFMs, with an EMI SE of 30–35 dB.…”
Section: Introductionmentioning
confidence: 99%
“…The application of magnetic nanofillers in enhancing the EMI shielding performance of NFMs has been widely reported. This is because their quantum size effect, natural resonance, and microcurrent properties can improve the magnetic loss and electromagnetic shielding performance of composite NFMs. In the work of Yang et al, a bifunctional electrospun NFM (33 μm thickness) was reported, whose surface was modified with Fe 3 O 4 nanoparticles (NPs) and MXene nanosheets, demonstrating an excellent specific shielding efficiency (SE) of 9212.1 dB cm 2 g –1 in the 8–26.5 GHz frequency range. Anwar et al used electrospinning technology to synthesize CoFe 2 O 4 /C NFMs, with an EMI SE of 30–35 dB.…”
Section: Introductionmentioning
confidence: 99%
“…However, conventional electromagnetic shielding materials primarily rely on reflecting electromagnetic waves, leading to the propagation of a large amount of reflected electromagnetic waves in space, which may continue to interfere with unshielded devices, resulting in secondary electromagnetic wave pollution. 8 Despite the extensive application of traditional metal materials in the field of electromagnetic shielding, they have some inherent limitations. For instance, their considerable weight and volume restrict the lightweight design in portable or wearable devices; their high rigidity makes them difficult to bend or shape, which is not conducive to achieving flexible or customized shielding solutions; the difficulty in processing increases manufacturing costs and time; they are susceptible to corrosion, which reduces shielding effectiveness and may cause secondary pollution; impedance matching issues lead to increased reflection of electromagnetic waves, affecting the shielding effect; high surface reflection rates increase the possibility of secondary reflection; they have single functions, mainly providing shielding effects without other additional functions; and poor environmental adaptability, which can lead to performance degradation under extreme conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic shielding materials typically block electromagnetic wave propagation by either reflecting incident electromagnetic waves or absorbing the electromagnetic wave energy entering the material and converting it into heat, gradually dissipating energy and reducing the penetration rate of electromagnetic waves. However, conventional electromagnetic shielding materials primarily rely on reflecting electromagnetic waves, leading to the propagation of a large amount of reflected electromagnetic waves in space, which may continue to interfere with unshielded devices, resulting in secondary electromagnetic wave pollution . Despite the extensive application of traditional metal materials in the field of electromagnetic shielding, they have some inherent limitations.…”
Section: Introductionmentioning
confidence: 99%